2023
DOI: 10.1007/s12649-023-02036-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Microbial Load of Digestate by the Cultivation of Galdieria sulphuraria Under Acidic Conditions

Abstract: Purpose Organic waste streams with a high microbial load have been used as nutrient sources in the cultivation of heterotrophic microalgae. However, it remains unclear whether an alga-based organic waste utilization can also result in a reduction of the microbial load, and thus in a combined waste utilization and hygenization process. Methods The heterotrophic cultivation of the microalga Galdieria sulphuraria at a pH of 2 and 45 °C as hygenization method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, the growth of the yeast cells could be kept under control and G. sulphuraria was the dominant species. Nevertheless, the results shown here (where yeasts were dominant) and earlier [20] (where spores were dominant) indicate the importance of a hygenization process that works independently of the applied substrates. The acidic growth conditions did not diminish all the organisms and allowed for control of them.…”
Section: Sanitation Of Waste Streamsmentioning
confidence: 41%
See 3 more Smart Citations
“…However, the growth of the yeast cells could be kept under control and G. sulphuraria was the dominant species. Nevertheless, the results shown here (where yeasts were dominant) and earlier [20] (where spores were dominant) indicate the importance of a hygenization process that works independently of the applied substrates. The acidic growth conditions did not diminish all the organisms and allowed for control of them.…”
Section: Sanitation Of Waste Streamsmentioning
confidence: 41%
“…In a previous study, it was shown that, during the hydrolysis of digestate and the cultivation of G. sulphuraria, the counts of aerobic, mesophilic organisms could be subsequently reduced by a log reduction factor of 3. The remaining microorganisms were almost exclusively spore-forming ones, which were reduced by a log reduction factor of 2 during cultivation under acidic conditions [20]. In this study using non-sterile food waste hydrolysate, only a few spore-forming microorganisms and no pathogens were found.…”
Section: Sanitation Of Waste Streamsmentioning
confidence: 51%
See 2 more Smart Citations